User experience: impact occupational factors on safety and health through ergonomic approach among older taxi drivers community in Malaysia - Mohd Yusoff, Irwan Syah; Ismail, Muhammad Heikal; Abu Bakar, Elistina (Human Resource Management Academic Research Society, 2021)
Background: One of the alternative professions that may include the older community is taxi drivers. Subsequently, they have to take explicit thought during driving activities as indicated by their capacity and ability to sustain their lives while minimizing health problems and increasing safety. Therefore, this paper aimed to study from a user experience the impact occupational factors on safety and health by an ergonomic approach among older community taxi drivers in Malaysian. Methods: A cross-sectional study was led utilizing a selfadministered survey instrument. Purposive method sampling used based on inclusive criteria; age 60 years old and above, self-driving taxi more than one year, no disabilities and registered with Ministry of Transport (MOT). A total of 443 respondents participated in the study. SPSS software version 20.0 to analyse the data. Results: More than half of the respondents (70.0%) felt back pain in the past 12 months, and 75.4% in the last seven days. There is a significant relationship health problem (p< 0.05) between variables; BMI, smoking status, carrying luggage into the trunk, supporting of the backrest for the whole body, the effect of the seat size on comfortable driving, feeling of back pain is mainly due to the seat design and longdistance driving and driving posture analysis at the high-risk position and awkward body posture on seat design during handling task. Conclusion: The low implication awareness on ergonomics education could increase health problem and decrease safety while handling the task among older taxi driver’s community in Malaysia.